‘Profitable for the country’. An Australian historical perspective of the contested purpose of public universities - Pitman, Tim (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This article analyses the social contract formulated between state and university, in the period 1850–1930. Using contemporary records–for example, legislation, parliamentary debates, university acts, newspaper articles, senate and professorial board minutes, and similar–this article examines how Australia’s early scholarly community contested and negotiated what it believed to be the purpose of higher education, with a sometimes-conflicting view held by the state. The analysis indicates that, from the outset, certain paradoxes have inscribed into these foundational negotiations. Conflicting narratives of opportunity and privilege positioned universities, simultaneously, as agents for social inclusion and maintainers of social privilege. The purpose of knowledge as either/both pure and practical has been another point of contestation. Consequently, universities vacillate between acts of social conservatism and progressivism. These tensions remain apparent in the modern purpose of higher education institutions.